ON CRIMINOLOGICAL PSYCHOLOGICAL DIFFERENTIATION OF JUVENILE OFFENDERS - M. Kaledin (Гуманитарные и юридические исследования)
The study discusses the feasibility and effectiveness of the typology of juvenile offenders. Differentiation (typology) is considered as a tool for forecasting, minimizing and preventing possible criminal attacks in the future. The author proposes a typology of criminals based on psychological and motivational criteria of the crime and identifies two main types of criminals: expansive (instinctive) and consequent criminals, each of which differentiates into subtypes based on the characteristics of the psychological portrait of the person, motivation and ideas as criteria for committing a crime. The author proposes to amend the current version of article 421 of the code of Criminal procedure in the context of imposing the obligation to conduct a comprehensive psychological and psychiatric examination of a minor, due to the existence of many diseases that occur latently and are diagnosed only by a specialist. The author proposes the development of specialized socio-pedagogical rehabilitation programs in the framework of forensic medical examinations, which should be addressed to law enforcement oficers in cooperation with minors, which, according to the author of the study, will contribute to a more effective re-socialization of juvenile offenders. The author also proposed the launch of specialized free courses aimed at psychological and pedagogical correction of convicted minors, which will include the study of internal personal contradictions, children's injuries, complexes and other negative phenomena. These courses can be conducted on the basis of psychiatric hospitals, clinics of border states, and as teachers (coaches) could be students-trainees. Thus, the competent typology of juvenile offenders, the creation of favorable conditions and the adoption of effective measures in the compartment can contribute to the real "recovery" of a person who has embarked on a criminal path.